Choice of Financing Source in International Debt Markets - Esho, Neil; Lam, Yung; Sharpe, Ian G. (Journal of Financial Intermediation, 2001)
This paper examines incremental debt financing decisions of large Asian firms over the period 1989–1998. We find that flotation costs, agency costs, and renegotiation and liquidation risk affect the choice of debt type and that firms in countries with well developed private bond markets have a higher probability of accessing international bond markets. Significant differences exist between the determinants of choice of debt type across Japanese and non-Japanese firms that cannot be explained by keiretsu associations. Moreover, there is no significant difference in the determinants of financing source for Japanese firms across independent firms, horizontal keiretsus, and vertical keiretsus. Journal of Economic Literature Classification Number: F39, G15, G21, G32.